Answer:
![y=(7)/(2)x-20](https://img.qammunity.org/2020/formulas/mathematics/middle-school/dfjc6zb41cditu2yiqo9beq2tczkw96bqx.png)
Explanation:
Let the equation of the line be
where, 'm' is its slope and
is a point on it.
Given:
The equation of a known line is:
![y=-(2)/(7)x+9](https://img.qammunity.org/2020/formulas/mathematics/middle-school/qycsyo42567pk9llhsfypdwxeyi52c4nkv.png)
A point on the unknown line is:
![(x_1,y_1)=(4,-6)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/chhv9szy18pwzbvyiw9nabpd9shnnprkam.png)
Both the lines are perpendicular to each other.
Now, the slope of the known line is given by the coefficient of 'x'. Therefore, the slope of the known line is
![m_1=-(2)/(7)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/lshkl0jt4h11eyoi8y9izcsv9ed1t259od.png)
When two lines are perpendicular, the product of their slopes is equal to -1.
Therefore,
![m\cdot m_1=-1\\m=-(1)/(m_1)\\m=-(1)/((-2)/(7) )=(7)/(2)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/kdpz5lvayj0d1q1rx7d6g1b5sw92lln6r3.png)
Therefore, the equation of the unknown line is determined by plugging in all the given values. This gives,
![y-(-6))=(7)/(2)(x-4)\\y+6=(7)/(2)x-14\\y=(7)/(2)x-14-6\\\\y=(7)/(2)x-20](https://img.qammunity.org/2020/formulas/mathematics/middle-school/gae8gm88qmfls20ujbshyem2g6b3b4ydgk.png)
The equation of a line perpendicular to the given line and passing through (4, -6) is
.